Bringing ecological economics into the regulatory process: the Manitoba experience. (12th October 2006) - Miller, Peter; Weiss, Steven; Taylor, Amy; McCulloch, Matthew
Since 2002, ENGOs Time to Respect Earth's Ecosystems (TREE) and Resource Conservation Manitoba (RCM) have intervened half a dozen times before Manitoba's Clean Environment Commission (CEC) in an environmental assessment) and Public Utilities Board (PUB) (in rate hearings) in reviews of Manitoba's crown electricity and gas utilities and public insurance corporation. We offer this case study of our 2005 Centra Gas rate intervention to illustrate the potential to apply ecological economics to the regulatory process. Our aim was to promote the application of principles of sustainability and social justice in the strategic planning, economic analysis, rates and DSM programming of this crown gas utility. To define sustainability, we invoked principles of Stewardship (intergenerational equity), Global Responsibility (economic, ecological and social interdependence) and Efficient Use of Resources (proper resource pricing, demand management, resource allocation, incentives and full-cost accounting) found in Manitoba's Sustainable Development Act (SDA). In addition, a socially just energy system must provide a limited amount of energy to meet basic needs. To introduce the concept of full-cost accounting, The Pembina Institute provided a limited and provisional life cycle costing of externalities (GHG impacts and alternative land use opportunity costs) and resource depletion associated with the provision and consumption of natural gas in Manitoba. The most conservative of Pembina's values (1.36/GJ) plus estimates of avoided transmission and distribution costs (0.50/GJ) and 'pecuniary benefits' from conservation (0.64/GJ) yielded an increment of 2.50/GJ to be added to the conventional embedded costs of gas supply to calculate a Marginal Value of Gas to Consumers (MVGC). The MVGC then: (1) becomes the marginal tailblock cost of gas in an inverted rate structure, (2) sets a threshold value for cost-effective conservation and fuel switching programmes and (3) underlies a self-funding feebate proposal for new gas service connections in which a connection charge is rebated for buildings meeting higher efficiency standards. The energy needs of the poor are addressed by implementing the targeted conservation measures and rate relief programmes (in addition to general DSM measures) characteristic of many jurisdictions in the US. Interventions like this are a practical way to shift energy policies, but they also point to issues in economic analysis and politics.